Biomaterials and engineering for implantology : in medicine and dentistry - Oshida, Yoshiki; Miyazaki, Takashi (Dr.) (De Gruyter, 2022)
Biomaterials are composed of metallic materials, ceramics, polymers, composites and hybrid materials. Biomaterials used in human beings require safety regulations, toxicity, allergic reaction, etc. When used as implantable materials their biological compatibility, biomechanical compatibility, and morphological compatibility must be acessed. This book explores the design and requirements of biomaterials for the use in implantology.
Keywords: Dental implants.; Dental materials.; Biomedical engineering.; elektronické knihy; electronic books